Penerapan Layanan Konseling Kelompok pada Siswa Terisolir Kelas X dI SMA Negeri 1 Indralaya Utara - Santiria, Silvia; Syarifuddin; Harlina (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2017)
This study aimed to determine the application of group counseling services for the isolated students at SMAN 1 North Indralaya. This type of research was the applied research with descriptive approach. Data were collected in this study using observation guidelines and analyzed descriptively qualitative. In this study there were 7 (seven) students were chosen as subjects from different class X. In the process of applyed the group's counseling service to discuss 1 (one) problems experienced by students named DS. The result of this study indicated that the DS experienced a change in mindset and attitude to improve their social relation in class. The implementation of group counseling services was not optimal yet, but the result of this study could be used as an alternative problem-solving for students who were isolated. Group counseling services could be also implemented to help students to reach maturity social accomplished development task students isolated.